Distribution and risk factors of canine heart diseases and survey for owners treatment intention - Noordin, Norhidayah (2023)
Heart disease accounts for up to 10.0% of canine cases reported in a primary veterinary healthcare centresoverseas. Risk factors may assist clinicians in establishing a differential diagnosis and planning a diagnostic approach. Early detection and treatment of heart disease had been shown to improve quality of life and prolong lifespan. This study reports the distribution and risk factors of canine heart disease and the survivability of dogs diagnosed with degenerative mitral valve disease (DMVD). The level of awareness, knowledge, and factors affecting the intention to treat canine heart disease among local dog owners were also investigated. Records of all dogs presented to the University Veterinary Hospital (UVH) between July 2013 and July 2020 were retrospectively analysed through logistic regression. The distribution of canine heart disease patients in this population is (n=734, 7.9%). Most of these dogs had acquired valvular disease (n=528, 76.0%) and DMVD (n=291, 38.0%) was the most common valvular affliction, followed by heartworm disease (n=113, 14.8%) and dilated cardiomyopathy (DCM) (n=90, 11.6%). The risk factors identified were gender, age group and breed size. Senior (Odds ratio, OR 3.54, p<0.001), and small breed (OR 6.74, p<0.001) dogs had a higher risk for valvular disease, while the large breed (OR 7.18, p<0.001) dogs had a greater risk for heartworm disease. Male (OR 1.83, p=0.02) and large breed (OR 3.12, p<0.001) dogs were at risk for DCM. A total of 261 respondents who owned or had experience caring for dogs were recruited to determine their level of awareness and knowledge of canine heart disease. The respondents’ intentions to treat were investigated using the Theory of Planned Behavior (TPB) items: attitude, subjective norm, and perceived behavioural control (PBC). Empathic concern was made as a moderator through the partial least squares method. Most of the respondents (83.5%) claimed that they were aware of the disease, however, their ability to identify clinical signs was fair. Most dog owners (92.3%) were willing to seek treatment if their pet dogs were diagnosed, but the cost (39.5%) was a primary concern for long-term treatment. Attitude, subjective norms, and PBC were significant predictors of the intention to treat. Females and owners with good knowledge of canine heart disease have a higher intention to treat it. Owners with low empathic concern can be motivated to treat affected dogs by cultivating their PBC. The survival of dogs diagnosed with DMVD was further investigatedby the Kaplan-Meier curve. Males (n= 156, 51.0%) senior-aged (n= 256, 84.7%), and small breed (n=258, 79.4%) dogs were frequently affected. Small breed dogs (OR: 3.95,p <0.001) were more likely affected by the disease compared with other breed sizes. Out of the total, 126 DMVD dogs (50.8%) had cardiac-related death. Dogs with treatment compliance had a longer median survival time (MST) (P<0.05). With compliant owners, MST of the dogs was 42.1 months (95% CI 35.7-48.5), and 25.2 months (95% CI 17.2-33.2) for stage C and stage D respectively. In conclusion, gender, age group, and breed size were significant predictors for the likelihood of heart diseases in dogs and are best applied in the context of specific heart diseases. Compliance with long-term treatment significantly improved the lifespan of DMVD dogs. Veterinarians may play an essential role in motivating owners’ intention to treat through education, support, and guidance, especially in terms of tasks perceived as challenging by the owners.